2004
DOI: 10.1086/381504
|View full text |Cite
|
Sign up to set email alerts
|

Oral Human Papillomavirus Infection in Adults Is Associated with Sexual Behavior and HIV Serostatus

Abstract: The prevalence and risk factors for oral human papillomavirus (HPV) infection are unknown, despite evidence for an etiological role for HPV in oral cancers. Oral samples from human immunodeficiency virus (HIV)-seronegative (n=396) and HIV-seropositive (n=190) adults were tested for HPV DNA. High-risk HPV infections were present in 2.1% of tonsil and 6.3% of oral-rinse specimens. The prevalence of oral high-risk HPV infection was greater in HIV-seropositive individuals (13.7% vs. 4.5%; P<.001). In multiple logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
267
11
12

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(318 citation statements)
references
References 64 publications
28
267
11
12
Order By: Relevance
“…22 This increase can probably be explained, in part, by a change in sexual behaviors and an increase in the number of sexual partners. Kreimer et al 29 found that the OR of oral HPV infection, detected by isolating HPV DNA from oral rinses among HIV-positive and HIV-negative adults, was higher in participants who reported Ͼ 1 oral sex partner in the previous year (OR ϭ 12.8; 95% CI, 3.1-53). 29 In a study of oral carcinoma risk in relation to sexual history and evidence of HPV infection, other investigators found that the risk of oral carcinoma increased significantly with decreasing age at first intercourse, increasing number of sexual partners, and a history of genital warts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 This increase can probably be explained, in part, by a change in sexual behaviors and an increase in the number of sexual partners. Kreimer et al 29 found that the OR of oral HPV infection, detected by isolating HPV DNA from oral rinses among HIV-positive and HIV-negative adults, was higher in participants who reported Ͼ 1 oral sex partner in the previous year (OR ϭ 12.8; 95% CI, 3.1-53). 29 In a study of oral carcinoma risk in relation to sexual history and evidence of HPV infection, other investigators found that the risk of oral carcinoma increased significantly with decreasing age at first intercourse, increasing number of sexual partners, and a history of genital warts.…”
Section: Discussionmentioning
confidence: 99%
“…Kreimer et al 29 found that the OR of oral HPV infection, detected by isolating HPV DNA from oral rinses among HIV-positive and HIV-negative adults, was higher in participants who reported Ͼ 1 oral sex partner in the previous year (OR ϭ 12.8; 95% CI, 3.1-53). 29 In a study of oral carcinoma risk in relation to sexual history and evidence of HPV infection, other investigators found that the risk of oral carcinoma increased significantly with decreasing age at first intercourse, increasing number of sexual partners, and a history of genital warts. 30 However, these authors used the SEER grouping that comprises SCC of the tongue, gum, floor of mouth, and "other/unspecified part of the mouth, tonsils, or oropharynx."…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, oral HPV infection has recently been associated with sexual behavior, in particular with number of oral sex partners. 90,91 Young age at first intercourse, number of lifetime sexual partners, a history of genital warts, 92 and ever performing oral sex 79 were associated with oral cancer risk in men. Risk among women was associated with number of lifetime sexual partners.…”
Section: Sexual Behavior and Human Papillomavirus Infectionmentioning
confidence: 99%
“…There is greater likelihood for HIV patients to be infected with more than one of the HPV genotypes (5.8 % compared to 1.5% of immunologically competent individuals) and with a genotype of high oncogenetic risk, such as HPV-16 for example, which is related to tonsillar cancers. Oral warts are rare in immunologically competent individuals, but are a regular finding in HIV patients with HPV (25,42).It is appropriate and advisable to test the levels of the three viruses (HPV, EBV and HSV) in patients with HIV, as well as to monitor their specific manifestations in the oral cavity. …”
Section: Hpv Ebv and Hsvmentioning
confidence: 99%